Two Genome Sequences of Klebsiella pneumoniae Strains with Sequence Type 23 and Capsular Serotype K1 - Lin, Hsi-Hsu (Genome Announc, 2016)
Here, we report the whole-genome sequences of Klebsiella pneumoniae ED2 and ED23, isolated, respectively, from bacteremic patients with liver abscesses (ED2) and patients with primary liver abscess and metastatic meningitis (ED23). Both strains were of multilocus sequence type 23 with capsule serotype K1.